2020
DOI: 10.1002/poc.4127
|View full text |Cite
|
Sign up to set email alerts
|

A study on the aromaticity and conjugation pathways of diheterodiazuliporphyrins and their dications

Abstract: The aromaticity of a series of diheterodiazuliporphyrins, both in the neutral and the dicationic states, has been investigated using the topological resonance energy (TRE) method. Our TRE results show that in each of the dicationic states, all the diheterodiazuliporphyrin isomers have greater aromaticity than when in their corresponding neutral states. An evaluation of the local aromaticity and of the main aromatic conjugation pathways has been carried out through the use of the bond resonance energy (BRE) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In general, large circuits make proportionately large contributions to overall RCs, whereas small circuits make small contributions. [ 35 ] However, for polycyclic neutral oxocarbons, according to the results in Tables 2 and S1, it is obvious that in all cases, large circuits make only a small aromatic contribution and a small CC contribution to these molecules. That is to say, in these compounds, the magnitude of the RC does not directly correspond with the size of the circuits.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, large circuits make proportionately large contributions to overall RCs, whereas small circuits make small contributions. [ 35 ] However, for polycyclic neutral oxocarbons, according to the results in Tables 2 and S1, it is obvious that in all cases, large circuits make only a small aromatic contribution and a small CC contribution to these molecules. That is to say, in these compounds, the magnitude of the RC does not directly correspond with the size of the circuits.…”
Section: Resultsmentioning
confidence: 97%
“…In the continuation of our work on the aromaticity of polycyclic heteroaromatic compounds, [ 35 ] we investigated some of the polycyclic neutral oxocarbons. Toward that end, we selected two descriptors to predict the global aromaticity of a series of polycyclic neutral oxocarbons: the TRE approach (an energetic index), [ 24–27 ] and the RC approach (a magnetic index).…”
Section: Introductionmentioning
confidence: 99%
“…At a fundamental level, this transformation is intriguing since the non-benzenoid aromatic tropylium ring is altered into the aromatic benzene ring [108]. Using the topological resonance energy (TRE) method, Tuerhong, M., and Kerim, A., investigated the aromaticity of a series of diheterodiazuliporphyrins in both neutral (56a) and dicationic states (56b) [109]. The TRE results indicated that all isomers of diheterodiazuliporphyrins exhibited greater aromaticity in the dicationic states compared to their corresponding neutral states.…”
Section: Complex Molecule Synthesismentioning
confidence: 99%
“…In the neutral states, the azulene units were the primary contributors to global aromaticity, and the compounds were primarily stabilized by their 10π-electron peripheral structures. However, in their dicationic states, the main contributors to global aromaticity were the 6π-electron tropylium unit structures [109] (Figure 23). The tropylium ion and its derivatives extend their applications in host-guest chemistry and polymerization chemistry.…”
Section: Complex Molecule Synthesismentioning
confidence: 99%
See 1 more Smart Citation